SCIENTIFIC AND METHODOLOGICAL SUPPORT IN PARALYMPIC SPORTS - Vorobev S.A.; Baryaev A.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to improve the content of the system of scientific and methodological support for Paralympic sports, taking into account the results of application practice. Methods and structure of the study. The analysis of the practice of using scientific and methodological support was carried out taking into account the accumulated experience of the Saint-Petersburg scientific-research institute for physical culture (FSBI SPbNIIFK), whose employees constantly take part in activities for the scientific and methodological support of the Russian Paralympic teams. Results and conclusions. An analysis of the practice of applying scientific and methodological support in Paralympic sports shows that when working with Paralympic athletes, it is necessary to use an individual approach in the formation of sports training programs, taking into account the nosological characteristics of athletes. To this end, it is necessary to constantly monitor the means and methods with a comparison of the performed and planned workload. This approach will allow you to make prompt adjustments to the system of sports training.